COMPARATIVE STUDY ON JUVENILE CHARACTERISTICS OF SELECTED LOCAL ACCESSIONS OF PAWPAW SEEDLINGSS IN OWERRI WEST WITH RED ROYALE - Nze, E. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The experiment was conducted at the Teaching and Research Farm of the School of Agriculture and Agricultural Technology, Federal University of Technology Owerri, to study the juvenile characteristics of selected local accessions of pawpaw seedlings. The treatments consisted of six local accessions of pawpaw from Owerri West L.G.A of Imo State and one improved variety namely; ACC-EZ, ACC-IH, ACC-NE, ACC-OB, ACC-IR, ACC-OR and RED ROYALE. These were laid out in a Completely Randomized Design (CRD) and replicated three times. Data were collected on viability and growth parameters. Results of the study indicated that, the improved variety (Red Royale) performed better than local accessions in terms of viability attributes by producing the highest number of emerged seedlings on the first day, attained 50% emergence within the shortest time and recorded the highest percentage emergence at 6 weeks with mean value of 91.80%. ACC-IH produced the highest number of leaves at 24 and 32 days after emergence with mean values of 13.33 and 23.00 each. ACC-OR performed better than other local accessions including the Red Royale in terms of increase in plant height at 8, 16, 24 and 32 days after emergence with mean values of 5.37, 8.37, 12.70 and 15.37 cm respectively. Furthermore, ACC-IH produced the thicker stem at 16 and 32 days after emergence with mean values of 0.5 and 1.5 cm each. From this research, it was clearly observed that some of the local accessions such as ACC-EZ, ACC-IH and ACC-IR exhibited superior juvenile characteristics either at per or above the improved variety (Red Royale) and therefore should be used by rural farmers within this area for mass propagation to maximize profit and at the same time be utilized by breeders for improvement purposes.